The importance of nursing professional values from undergraduate nursing students' perspective - Nini Asfaw Negash (Elsevier, 2023)
Background: Professional values are foundational to professional nursing practices and necessary for all members of a profession and for appropriate nursing practice. Nursing student's perception of the importance of professional values has a great impact on provision of safe patient care. Despite this, the issue had not been sufficiently addressed in Ethiopia. This study aims to assess the importance of professional nursing values from undergraduate nursing student's perspective at University of Gondar specialized hospital. Method: Institution based cross-sectional study design was conducted in University of Gondar specialized hospital. Data was collected from 211undergraduate nursing students using a pre-tested, structured and self-administered English version questionnaire. EPI Info 7 was used for data entry and SPSS version 22 for analysis. A binary logistic regression model was utilized to identify factors associated professional values of nursing students. An adjusted odds ratio with 95% confidence interval was computed to determine the level of significance. Result: More than half (54.5 %) of the respondents had high awareness and perception of the importance of professional values while the remaining (45.5 %) had low awareness and perception of the importance of professional values. Academic year [AOR = 5.5, 95 % CI (2.21, 8.33)], and training [AOR = 2.5, 95 % CI (1.92, 5.21)], had a positive and significant association with nursing students perception of professional values. Conclusion: Nearly (45.5%) of undergraduate nursing students in Ethiopia had low awareness and perception of the importance of professional values. Therefore, it is suggested that nursing students should be able to apply professional values in making decisions when dealing with ethical challenges in the healthcare area. It is also proposed that, strategies should be developed to improve weaknesses of nursing students in the professional values.